Day 3 Wed, November 14, 2018 2018
DOI: 10.2118/192824-ms
|View full text |Cite
|
Sign up to set email alerts
|

Fibre Optic Surveillance for Conformance Monitoring in a Polymer Pilot by Petroleum Development Oman

Abstract: Petroleum Development Oman (PDO) has been utilizing several Enhanced Oil Recovery (EOR) methods in the Sultanate of Oman to accelerate (polymer/steam floods) and increase (Alkaline Surfactant Polymer, or ASP, floods) recovery from fields with challenging rock and fluid properties. Polymer-flood is a mature EOR technique, and has been trialled and implemented successfully on full-field scale in a sandstone reservoir of excellent quality in the South of Oman. As part of this continuing effort, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Many successful polymer EOR project reviews have been reported in the literature ,, (Figure ). PF is effective for oils with viscosities less than 126 mPa·s and reservoir temperatures up to 110 °C, oil viscosity less than 100 mPa·s, with low reservoir temperatures (<95 °C), viscous oils ranging from 150 to 200 mPa·s with a maximum temperature of 70 °C, and oils with viscosities as high as 8400 mPa·s in heavy oil reservoirs .…”
Section: Screening Criteria and Limitations Of Swp In Heavy Oil Sands...mentioning
confidence: 99%
“…Many successful polymer EOR project reviews have been reported in the literature ,, (Figure ). PF is effective for oils with viscosities less than 126 mPa·s and reservoir temperatures up to 110 °C, oil viscosity less than 100 mPa·s, with low reservoir temperatures (<95 °C), viscous oils ranging from 150 to 200 mPa·s with a maximum temperature of 70 °C, and oils with viscosities as high as 8400 mPa·s in heavy oil reservoirs .…”
Section: Screening Criteria and Limitations Of Swp In Heavy Oil Sands...mentioning
confidence: 99%
“…DAS was firstly applied for hydraulic fracture monitoring in tight gas well [3] . Controlled experiments and field trials of DAS for other applications in water injection, gas injection, gas producer and high-rate gas-oil ratio producer wells then were carried [4], [5], [6], [7] . To improve the performance of DAS, cointerpretation of DTS and DAS data has been proposed to calculate the fluid flow rate and its composition in smart wells equipped with Inflow Controls Valves [8] .…”
Section: Introductionmentioning
confidence: 99%